Flexural Strength and Ductility of Concrete Brick Masonry Wall Strengthened using Steel Reinforcement. (2015) - Triwiyono, Andreas; Nugroho, Arif S.B.; Firstyadi, Athanasius D.; Ottama, Faris
Abstract: In some areas, most of the damaged buildings caused by earthquakes were residential houses. The damages affect the number of casualties and socio economic losses. Most of residential houses in some countries are made of masonry walls. Because of the material cost and simple construction method, concrete brick masonry walls become widely used in Indonesia. Improving the structural performance of this kind of wall has become important. For this reason, experimental test was conducted on the flexural strength and ductility of concrete brick masonry wall strengthened by steel bar reinforcement. The concrete bricks are in the form of cellular hollow concrete blocks which used for practical residential houses popularly. The aims of the test were to determine the out of plane flexural capacity and ductility of the strengthened masonry walls by using some variation steel bars reinforcement ratio in horizontal and vertical directions of the walls. The results of the test showed that the variations of flexural strength of unreinforced wall specimen were very high. The flexural capacity and ductility of strengthened walls were increased significantly, up to 5-16 times higher than that of non strengthened walls. Steel reinforcement could increase the flexural strength close to the theoretical. Although they failed brittle, the both materials bataton bricks and steel reinforcements were non easily separate one to another.